Homo Imperii : A History of Physical Anthropology in Russia - Mogilʹner, Marina (Book collections on Project MUSE., 2013)
It is widely assumed that the "nonclassical" nature of the Russian empire and its equally "nonclassical" modernity made Russian intellectuals immune to the racial obsessions of Western Europe and the United States. Homo Imperii corrects this perception by offering the first scholarly history of racial science in prerevolutionary Russia and the early Soviet Union. Marina Mogilner places this story in the context of imperial self-modernization, political and cultural debates of the epoch, different reformist and revolutionary trends, and the growing challenge of modern nationalism.